Botswana : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The major trends in terms of GDP growth rates, conditions of market forces, and the core inflation crisis in Botswana are analyzed in detail in the report. It has been suggested that although the recovery from the financial crisis of Botswana is the strongest compared with other middle-income countries, the overall results do not point toward a positive development in the economy. The need for authorities to take up certain measures and modify their methods of functioning is pivotal to Botswana's survival in the existing fragile economic environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet